Trouble in the Psychosphere: HBO’s True Detective (2014) as a Hybrid Genre. - Lopes, Elisabete (2020)
Recently, many contemporary TV shows have raised the stakes as far as the quality of their contents is concerned. They welcomed certain challenges that contributed to lend them the status of cult series. True Detective (2014) certainly forms part of this selective group. Nic Pizzolatto, the creative mind behind True Detective (2014), decided to take up all these challenges and ended up by creating a hybrid show in the sense that it gathers elements of Gothic genre, weird fiction, criminal investigation, and film noir that, once mixed up, paved the way to the upcoming success. Other feature that fuels True Detective‟s allure lies precisely in the ties that it openly shares with literature, since it purports references that point to well-known oeuvres or authors. In this light, it is the purpose of this essay to examine how Pizzolatto‟s eclectic recipe combine its ingredients that result in a TV show anchored upon the parameters of originality and quality. The undeniable quality of True Detective (2014) goes beyond the well-thought script, Adam Arkapaw‟s mesmerizing photography, the protagonists‟ amazing performance, and the careful direction of Cary Fukunaga. It has become a true postmodern visual monster that unexpectedly came straight from the Lousiana bayous to haunt us, bringing along an aura of cosmic horror that, interlinked with suspense and criminal investigation, will relentlessly take a grip on us.